1 & 2 Chronicles a message for Yehud : an introduction and study guide - Allen, Leslie C. 1935- (London New York T&T Clark, 2021)
1. Context -- 2. Interpretations -- 3. Authorship -- 4. Themes -- Bibliography -- Index.
"Leslie Allen introduces students to the 1 & 2 Chronicles in the Old Testament, incorporating insights from over two decades of previous scholarship while grounding her analysis in earlier key works. 'A Message for Yehud' sums up what has been judged to be a fundamental motivation underlying the whole book, a conviction that the obligation to 'seek the Lord' in the light of the Torah and prophetic texts must be laid on the hearts of the community of Yehud in the fourth century BCE. To this end, using Samuel-Kings as a basis, Chronicles reviewed pre-exilic royal history for positive and negative clues as to how the generation for which it was written might achieve this spiritual ideal. In the book, Allen shows how this program was communicated all through the book by literary and rhetorical means"--
Includes bibliographical references and index
Also issued in print: T&T Clark, 2021.
Reproduktion
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Bible -- Criticism, interpretation, etc; Theology; Old Testament / Hebrew Bible (Biblical Studies); Biblical Studies; Old Testaments; Electronic books